A Synergistic Strategy of Manipulating the Number of Selenophene Units and Dissymmetric Central Core of Small Molecular Acceptors Enables Polymer Solar Cells with 17.5 % Efficiency. (20th July 2021) - Yang, Can; An, Qiaoshi; Bai, Hai‐Rui; Zhi, Hong‐Fu; Ryu, Hwa Sook; Mahmood, Asif; Zhao, Xin; Zhang, Shaowen; Woo, Han Young; Wang, Jin‐Liang
Abstract: A dissymmetric backbone and selenophene substitution on the central core was used for the synthesis of symmetric or dissymmetric A‐DA′D‐A type non‐fullerene small molecular acceptors (NF‐SMAs) with different numbers of selenophene. From S‐YSS‐Cl to A‐WSSe‐Cl and to S‐WSeSe‐Cl, a gradually red‐shifted absorption and a gradually larger electron mobility and crystallinity in neat thin film was observed. A‐WSSe‐Cl and S‐WSeSe‐Cl exhibit stronger and tighter intermolecular π–π stacking interactions, extra S⋅⋅⋅N non‐covalent intermolecular interactions from central benzothiadiazole, better ordered 3D interpenetrating charge‐transfer networks in comparison with thiophene‐based S‐YSS‐Cl . The dissymmetric A‐WSSe‐Cl ‐based device has a PCE of 17.51 %, which is the highest value for selenophene‐based NF‐SMAs in binary polymer solar cells. The combination of dissymmetric core and precise replacement of selenophene on the central core is effective to improve J sc and FF without sacrificing V oc . Abstract : A dissymmetric backbone and selenophene substitution on the central core was employed to synthesize dissymmetric A‐DA′D‐A NF‐SMAs. Their detailed single‐crystal packing were revealed successfully. The dissymmetric A‐WSSe‐Cl:PM6 device presented an impressive PCE of 17.51 %, which is the highest values for selenophene‐based and the dissymmetric NF‐SMAs in binary PSCs.